Identification of the consistently altered metabolic targets in human hepatocellular carcinoma - Nwosu, Zeribe C.; Hammad, Seddik; Rössler, Stephanie; Ebert, Matthias; Meyer, Christoph; Dooley, Steven (Cellular and Molecular Gastroenterology and Hepatology, 2017)
Cancer cells rely on metabolic alterations to enhance proliferation and survival. Metabolic gene alterations that repeatedly occur in liver cancer are largely unknown. We aimed to identify metabolic genes that are consistently deregulated, and are of potential clinical significance in human hepatocellular carcinoma (HCC).
Gesehen am 26.10.2018